Desarrollo de habilidades blandas en el estudiantado mediante la actividad académica procesos prácticos para la formación de docentes en educación comercial - Guillén Cordero, Norieth (2020)
The purpose of this study is to demonstrate the soft skills that students of Commercial Education’s major at Universidad Nacional (UNA) have developed,through their participation as practicing teachers in the Actividad Académcia Procesos Prácticos para la Formación de Docentes en Educación Comercial,at the Escuela de Secretariado Profesional (ESP) of the Facultad de Ciencias Sociales and División de Educología of the Centro de Investigación y Docencia.To achieve the proposal, a descriptive mixed investigation was carried out, with the participation of students who developed their teaching processesfrom 2016, 2017, 2018 to 2019. It was found out that more than 95 % of the population considers that the teaching practices allowed them to developor enhance various soft skills. The most determining factor for that personal growth, was having to work with populations of elderlies and young people at social risk; in addition, it was possible to highlight the main soft skills acquired by the practicing students. Among them, patience and understanding, problem solving, teamwork, flexibility and adaptability stand out. It was concluded that although the intention of the teaching practices is that the practitioners assume the role of planners and mediators of the teaching and learning process, they must also deal with situations and scenarios that foster an enrichment of the practitioners not only at the academic and didactic level, but also attitudinal.